2022
DOI: 10.55519/jamc-03-9552
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hyperuricemia in Subjects With Unstable Angina/Myocardial Infarction and Their Prognosis

Amir Rashid Qureshi,
Syed Affan Ali,
Mir Jalal
et al.

Abstract: Background: Inhibition of nitric oxide synthesis and stimulation of smooth muscle proliferation by increased serum levels of uric acid play an important role in accelerated atherogenesis in the vessels of patients with hyperuricemia. The objective of the study was to determine the frequency of hyperuricemia in patients with acute coronary syndrome and their in-hospital outcomes. Methods: This cross-sectional study was conducted in the cardiology department of Ayub Teaching Hospital, Abbottabad fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…We observed mortality of 29.9% in our ICU population which was similar to some other ICUs of developing countries like India (30% in 2007, 46.2% in 2011, 28% in 2014, and 34% in 2018) 4 13 14 15 and Pakistan (28.7% in 2007), 7 albeit higher than ICUs of the western world with greater medical personnel, nursing staff, and specialized equipment. The expected mortality computed by PIM-2 score was 27.9% giving an SMR of 1.07 (95% CI: 0.79–1.41), which was almost equal to 1 but showed that PIM-2 score just slightly underpredicted mortality which was quite contrary to well-established centers which depicted overprediction by the model with SMR <1.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We observed mortality of 29.9% in our ICU population which was similar to some other ICUs of developing countries like India (30% in 2007, 46.2% in 2011, 28% in 2014, and 34% in 2018) 4 13 14 15 and Pakistan (28.7% in 2007), 7 albeit higher than ICUs of the western world with greater medical personnel, nursing staff, and specialized equipment. The expected mortality computed by PIM-2 score was 27.9% giving an SMR of 1.07 (95% CI: 0.79–1.41), which was almost equal to 1 but showed that PIM-2 score just slightly underpredicted mortality which was quite contrary to well-established centers which depicted overprediction by the model with SMR <1.…”
Section: Discussionsupporting
confidence: 83%
“…3 However, most of the well-developed centers had higher values of AUC including 0.9 from Australia and New Zealand 10 and 0.87 from Spain. 19 A previous study done in Lahore, Pakistan reported an AUC of 0.88 with a good calibration of the model, 7 as it was done in an ICU with a higher influx of cardiac and postsurgical patients and patient to nurse ratio of 1:1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A study carried out by M A Shaikh et al reported 25.5% prevalence of diabetic retinopathy amongst type 2 diabetes mellitus patients which is not in accordance with our study but they reported comparable frequency of Background retinopathy, Preproliferative retinopathy and Proliferative retinopathy by classifying cases of diabetic retinopathy 19 . A previous randomized control study reported 40.1% diabetic retinopathy prevalence amongst type 2 diabetes mellitus patients whic is almost same with our study findings 20 .…”
Section: Discussioncontrasting
confidence: 81%